ANALISIS PENGARUH PENERAPAN E-COMMERCE TERHADAP PENDAPATAN UMKM DI MASA PANDEMI (Studi Kasus Sektor Kuliner di Kota Malang) - Habiba, Ayunda Firdaus Chusnul; Prasetyia, Ferry (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The emergence of Covid-19 has caused a lot of harm MSMEs, especially since the government implemented social distancing. This causes people to experience changes in behavior patterns, one of the most visible of which is their consumption patterns, which were initially carried out face-to-face and had to change to other appropriate methods. This e-commerce actually existed even before the emergence of Covid-19, however, it was not very attractive to the public. For now, due to the implementation of government policies to maintain distance, e- commerce is one of the appropriate methods that can be used by MSMEs in overcoming the problem of declining MSME income. From the problems above, this study aims to determine how to analyze the influence of the application of e- commerce on MSME income during the Pandemic. This research focuses on SMEs in the culinary sector in Malang City. This study uses PLS analysis with the help of SmartPLS 3.0 software. The results of this study indicate that the variable length of business, HR, and competitiveness have a positive and significant effect on MSME income, while the variables of e-commerce implementation, and capital have no effect on MSME income.